Interprofessional Training: Preparing Graduate Counseling and Social Work Students for Integrated Behavioral Healthcare Settings. Issue 3 (4th May 2022) - Zanskas, Stephen A.; Brasfield, Michelle; Landry, Maggie; Taylor, Laura C.; Delavega, Elena; Neely-Barnes, Susan
ABSTRACT: Purpose: This study presents the evaluation of a Health Resources and Services Administration (HRSA) workforce development initiative focused on preparing master's level social work and counseling students to work in integrated behavioral healthcare settings. Method: Seventy-nine trainees attending a large urban university in the southeastern United States participated in an interdisciplinary program that included a combination of field experience, exposure to interdisciplinary professional settings, readings, and experiential-didactic sessions. Results: Differences across trainee areas of study, race, gender, and urban or rural origins were assessed utilizing pre/posttest measures on cultural competency, team skills, and attitudes toward family involvement. Conclusions: Results suggest that trainees demonstrated overall growth in team skills. Potentially an overlooked but positive outcome of the training program was the modeling of effective interprofessional teamwork through collaboration among the counseling and social work faculty. Implications for social work and counselor educators and future research are discussed.